The social stratification of the 2018 vote in Italy: between continuity and change. Issue 3 (2nd September 2018) - Maraffi, Marco
ABSTRACT: The massive vote shift in the 2018 elections, underlies a changed configuration of the social stratification of the vote. The end-result is one of an increased heterogeneity of the social bases of partisan support and of the contradictory social landscape parties are confronted with. Driven by the paramount salience of economic concerns among voters, labour market position and type of employment appear to be the main axes of stratification: self-employed voters massively supported the centre-right coalition and especially the Lega, attracted by the promise of huge tax cuts; but the Lega disproportionally attracted also manual workers with poor education. On the other hand, non-manual employees and skilled manual labour, with middle-level education, showed a clear propensity to vote for the M5s; which also revealed a huge appeal among unemployed, especially young, and inactive women. This social configuration of the vote is reflected in the clear-cut territorial divide of the vote: supremacy of the M5s in the Southern regions and predominance of the Lega in the North (and in some Central regions as well). The PD – the big loser of the elections in political terms –seems to have appealed especially to more socially established and secure social groups (Northerner, aged, educated employees and, above all, pensioners). This social stratification of the PD's vote is not a surprise and is in line with a long-running trend. It signals the relative unattractiveness of the PD for those social groups which think they are bearing the brunt of globalization's downside and feel inadequately protected and insecure in their daily lives.